Isotype Specific Assembly of B Cell Antigen Receptors and Synergism With Chemokine Receptor CXCR4 - Maity, Palash C.; Datta, Moumita; Nicolò, Antonella; Jumaa, Hassan (Frontiers in Immunology, 2018)
Expression of the membrane-bound from of the immunoglobulin (Ig) as part of the antigen receptor is indispensable for both the development and the effector function of B cells. Among five known isotypes, IgM and IgD are the common B cell antigen receptors (BCRs) that are co-expressed in naïve B cells. Despite having identical antigen specificity and being associated with the same signaling heterodimer Igα/Igβ (CD79a/CD79b), IgM and IgD-BCR isotypes functionally differ from each other in the manner of antigen binding, the formation of isolated nanoclusters and in their interaction with co-receptors such as CD19 and CXCR4 on the plasma membrane. With recent developments in experimental techniques, it is now possible to investigate the nanoscale organization of the BCR and better understand early events of BCR engagement. Interestingly, the cytoskeleton network beneath the membrane controls the BCR isotype-specific organization and its interaction with co-receptors. BCR triggering results in reorganization of the cytoskeleton network, which is further modulated by isotype-specific signals from co-receptors. For instance, IgD-BCR is closely associated with CXCR4 on mature B cells and this close proximity allows CXCR4 to employ the BCR machinery as signaling hub. In this review, we discuss the functional specificity and nanocluster assembly of BCR isotypes and the consequences of cross-talk between CXCR4 and IgD-BCR. Furthermore, given the role of BCR and CXCR4 signaling in the development and survival of leukemic B cells, we discuss the consequences of the cross-talk between CXCR4 and the BCR for controlling the growth of transformed B cells. Running Title: The plasma membrane organization and functional differences between IgM and IgD Key words: B cell antigen receptor (BCR); Chemokine receptor 4 (CXCR4); Nanoclusters; Cytoskeleton; B cell malignancies